Analisis Hukum Penerapan Dan Bentuk Tindak Pidana Pemilu Menurut Undang-Undang Nomor 7 Tahun 2017 - Yulia Nerise Fitriensi (Mediation : Journal Of Law, 2023)
Elections are held to elect members of the DPR, DPD and DPRD as well as elect the president and vice president. Quality elections can produce a government that is recognized and supported by the people. This research uses a qualitative method with a literature review and legislation approach. Data analysis was performed by descriptive analysis. The results of the study can be concluded that the general election is an order from the 1945 Constitution to implement the principle of people's sovereignty which is carried out every five years in the Republic of Indonesia with the aim of establishing a People's Consultative Assembly imbued with the spirit of Pancasila and the Constitution of the Republic of Indonesia; elect the people's representatives and the President and Vice President in continuing the struggle to defend and develop the aims of the State; elections are a means of implementing democracy to uphold the upholding of Pancasila and defending the 1945 Constitution of the Republic of Indonesia; as well as to guarantee the continuity of the five-year government and fill in the national development. Election crimes can be included in special crimes, namely election crimes and violations both regulated in the Criminal Code (KUHP) and regulated in Law Number 7 of 2017 concerning General Elections. The parties that can be accused of not having an election are: election organizers (KPU, Bawaslu, government); general election participants (Political Parties, Candidates for DPR, DPD, DPRD, Candidates for President and Vice President); the community as legal subjects (as voters, the Success Team including the community who invites them not to use their voting rights).